2017
DOI: 10.1016/j.ijrobp.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Medical Malpractice Claims Against Radiation Oncologists

Abstract: Purpose/Objective(s) We examined characteristics of medical malpractice claims involving radiation oncologists closed during a 10-year period. Methods and Materials Malpractice claims filed against radiation oncologists from 2003 to 2012 collected by a nationwide liability insurance trade association were analyzed. Outcomes included the nature of claims and indemnity payments, including associated presenting diagnoses, procedures, alleged medical errors, and injury severity. We compared the likelihood of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…1,10,[17][18][19][20] Most current literature pertaining to oncologic errors and adverse events has been based on closed claims malpractice data. 10,21,22 In those data, the primary reasons for litigation include failure to diagnose and treat, patient injuries, and failure to adhere to safety protocol. 10,21,22 Existing literature reports oncologic errors and adverse events in specific areas of oncology, including errors in chemotherapy and radiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10,[17][18][19][20] Most current literature pertaining to oncologic errors and adverse events has been based on closed claims malpractice data. 10,21,22 In those data, the primary reasons for litigation include failure to diagnose and treat, patient injuries, and failure to adhere to safety protocol. 10,21,22 Existing literature reports oncologic errors and adverse events in specific areas of oncology, including errors in chemotherapy and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…10,21,22 In those data, the primary reasons for litigation include failure to diagnose and treat, patient injuries, and failure to adhere to safety protocol. 10,21,22 Existing literature reports oncologic errors and adverse events in specific areas of oncology, including errors in chemotherapy and radiation. [4][5][6][7][8][9][10][11][12][13] Multiple studies revealed that medication errors, including ordering the wrong dose and failure to follow protocol when administering the drug, were the most commonly reported adverse event type in chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This outcome was selected as it was deemed by the authors relevant to motivating practice change and had face validity as a marker of malpractice environment, as well as consistency with methods used in other studies of malpractice environment. 11,[22][23][24] We chose variables a priori to include in the model. For claimant age, the odds ratio is per year.…”
Section: Discussionmentioning
confidence: 99%
“…Large privately owned databases managed by insurance associations have been used in medicolegal studies for other conditions and represent another potential source of data for malpractice litigation, however, these databases typically contain coded data using standardized definitions which limits the depth of information for each case. [20][21][22][23][24] In the absence of a single centralized, comprehensive database of all malpractice claims in the United States, Westlaw represents one of the best publicly available sources of malpractice data. This study defined search parameters for cases from 2010 to 2019, in order to capture comprehensive trends in spine litigation of the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cases in our study should be considered a subset of all malpractice claims involving spine surgery, specifically those that were deemed to have sufficient basis for trial involving higher monetary claims, which may be of greater relevance for physicians hoping to identify methods to improve patient care while reducing malpractice liability. Large privately owned databases managed by insurance associations have been used in medicolegal studies for other conditions and represent another potential source of data for malpractice litigation, however, these databases typically contain coded data using standardized definitions which limits the depth of information for each case 20–24. In the absence of a single centralized, comprehensive database of all malpractice claims in the United States, Westlaw represents one of the best publicly available sources of malpractice data.…”
Section: Discussionmentioning
confidence: 99%